(untitled) (Journal of the College of Basic Education, 2022)
Thermal loss coefficients of flat plate collector are mainly influenced by a large number of parameters. These parameters could be classified as design, operational and environmental, In this work the effects of some of these will considered, ambient temperature, wind velocity, tilt angle, air gap and absorber plate temperature. The results showed that values of losses coefficient using empirical correlation of Malhorta from (4.1- 12.2 W/m2.K) for ambient temperature at absorber plate temperature (25 and 70 °C), the loss coefficient was observed to increasing gradually (7.2 – 8.9) with increasing wind velocity at (1-5m/s), also the losses coefficient decreases (7.5- 5.5 W/m2.K) as the air gap spacing increasing (0.02- 0.1m), the losses factor progressively drops from (7.8-6.55 W/m2.K) with higher values of tilt angle (5-50 degree) and the results indicates that the losses coefficient increasing ( 7.32-7.8 W/m2.K) as the ambient temperature (10-60 °C) also increases.